Respuestas
Respuesta dada por:
0
La respuesta es esta:
(a-b) x (a-b) = (a-b)²
(a-b) x (a-b) = (a-b)²
Respuesta dada por:
0
es diferencia de cuadrados:
![(x - y) \times (x + y) = {x}^{2} + xy - xy - {y}^{2} \\ (x - y)(x + y) = {(x - y)}^{2} = {x}^{2} - {y}^{2} (x - y) \times (x + y) = {x}^{2} + xy - xy - {y}^{2} \\ (x - y)(x + y) = {(x - y)}^{2} = {x}^{2} - {y}^{2}](https://tex.z-dn.net/?f=%28x+-+y%29+%5Ctimes+%28x+%2B+y%29+%3D++%7Bx%7D%5E%7B2%7D++%2B+xy+-+xy+-++%7By%7D%5E%7B2%7D++%5C%5C+%28x+-+y%29%28x+%2B+y%29+%3D++%7B%28x+-+y%29%7D%5E%7B2%7D++%3D++%7Bx%7D%5E%7B2%7D++-++%7By%7D%5E%7B2%7D+)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años